Neurological Complications During Pulsatile Ventricular Assistance With the Berlin Heart EXCOR in Children: Incidence and Risk Factors. Issue 10 (5th April 2013) - Polito, Angelo; Netto, Roberta; Soldati, Massimiliano; Brancaccio, Gianluca; Grutter, Giorgia; Amodeo, Antonio; Ricci, Zaccaria; Morelli, Stefano; Cogo, Paola
Abstract The aim of this study is to describe the incidence of brain injury (BI) in children with end‐stage cardiac failure who were supported with the Berlin Heart EXCOR ventricular assist device (VAD) as a bridge to heart transplantation. Between January 2002 and January 2012, all patients <18 years of age who underwent the implantation of the Berlin Heart EXCOR at Bambino Gesú Children's Hospital were included. A total of 25 patients were included in this study. Median age and weight at implantation were 22.4 months (range 3.6–154.2) and 10 kg (range 4.5–36), respectively. Diagnosis included cardiomyopathy (n = 20) and congenital heart disease (n = 5). Eleven patients received atrial cannulation. Nine patients underwent biventricular assist device support. Seven patients underwent extracorporeal membrane oxygenation before the implantation of the EXCOR VAD. Median duration of VAD support was 51 days (range 2–167). Nine patients had evidence of acute BI including intracranial hemorrhage (n = 5) and cerebral ischemia (n = 4). Freedom from BI at 30, 60, and 90 days from VAD implantation was 80.7, 69.9, and 43.3%, respectively. Weight <10 kg at implantation was significantly associated with BI. BI is a frequent complication among children supported with EXCOR VAD and is associated with lower weight at implantation. However, our data do not support the association between size and BI. Future prospective multicenter studies are warranted to further help understand the etiology and the impact of BI and to improve functional outcomes for children undergoing EXCOR VAD mechanical support.